Design of Very High Throughput WLAN System for 4K Digital Cinema Transmission - Syafei, Wahyul Amien; Ochi, Hiroshi (Departemen Teknik Elektro, Universitas Diponegoro, 2009)
We proposed a design of a Very High Throughput Wireless LAN system. It reaches 33 meter propagation distance by using 80 Mhz bandwidth on 5 GHz band. The proposed preamble has backward compatibility with IEEE802.11n system, allows band sharing and avoids collision within 5 GHz band. The proposed preamble has comparable PAPR and preamble efficiency with IEEE892.11n system. Run test for transmitting 90 frames of 4K image size with 24 bit per pixel resolution for digital cinema simulation under in-door channel model demonstrates the excellent performance of the proposed system. Keywords: VHT WLAN, backward compatibility, PAPR, preamble efficiency, digital cinema transmission